The Impact of Online Learning through Students’ Mathematical Habit of Mind - Widyastuti Widyastuti; Santy Setiawati; Mella Triana (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
Online learning became one of the most popular learning strategies during the pandemic of Covid-19 in every level of education in Indonesia. This type of learning strategy certainly has an impact on developing student’s learning habit and also thinking habit. The impact of the implementation of online learning need to be measured to reveal the changes as the result of learning strategy which was adopted by the educators. This impact needs to be studied from the mathematical habit of mind as the point of view. The research method was survey research with population all students of mathematics education study program in Lampung University. Simple random sampling was used as the sampling technique to obtain 191 students in even semester of the 2019/2020 academic year as the sample. Data collected using questionnaire which measured variables self-perception mathematical habit of mind and implementation of online learning. Data analyzed using simple linear regression on α = 5%. Based on data analysis, it can be concluded that the equation of the regression that express the relationship of self-perception mathematical habit of mind (Y) and implementasion of online learning (X) is Y = 0,246 X + 38,572 which indicates that there are significant low impact of implementation of online learning on students self-perception mathematical habit of mind